2012
DOI: 10.1007/s12039-012-0286-5
|View full text |Cite
|
Sign up to set email alerts
|

Selenium dioxide catalysed oxidation of acetic acid hydrazide by bromate in aqueous hydrochloric acid medium

Abstract: Selenium dioxide catalysed acetic acid hydrazide oxidation by bromate was studied in hydrochloric acid medium. The order in oxidant concentration, substrate and catalyst were found to be unity. Increasing hydrogen ion concentration increases the rate of the reaction due to protonation equilibria of the oxidant. The mechanism of the reaction involves prior complex formation between the catalyst and substrate, hydrazide, followed by its oxidation by diprotonated bromate in a slow step. Acetic acid was found to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Selenium(IV) oxide-catalyzed oxidation of acetic acid hydrazide by bromate gives acetic acid as the oxidation product. Kinetic studies have shown that the reaction proceeds through formation of a complex between the catalyst and hydrazine which will be oxidized by the oxidant in a rate determining step [88]. Selenium(IV) oxide also catalyzes the oxidation of nicotinic acid hydrazide (NIH) by bromate in hydrochloric acid medium.…”
Section: Selenium(iv) Oxide and Selenic(iv) Acid As Oxidizing Agenmentioning
confidence: 99%
“…Selenium(IV) oxide-catalyzed oxidation of acetic acid hydrazide by bromate gives acetic acid as the oxidation product. Kinetic studies have shown that the reaction proceeds through formation of a complex between the catalyst and hydrazine which will be oxidized by the oxidant in a rate determining step [88]. Selenium(IV) oxide also catalyzes the oxidation of nicotinic acid hydrazide (NIH) by bromate in hydrochloric acid medium.…”
Section: Selenium(iv) Oxide and Selenic(iv) Acid As Oxidizing Agenmentioning
confidence: 99%
“…It is also a photoconductor with a low melting point ( ca 217 °C), a high refractive index and strong reactivity, resulting in functional materials such as Ag 2 Se and CdSe, 33 ZnSe and PbSe 34 . In numerous organic reactions, selenium dioxide (SeO 2 ) works as both an oxidant and a catalyst 35 . Tung et al 36 .…”
Section: Introductionmentioning
confidence: 99%
“…34 In numerous organic reactions, selenium dioxide (SeO 2 ) works as both an oxidant and a catalyst. 35 Tung et al 36 used APS as an oxidizing agent to explore the effect of dopant concentration on the structure and characteristics of selenious acid-doped PANI (PANI-SA). Amarnath et al 37 utilized selenious acid as a dopant and APS as an oxidizing agent in a template-free method to produce PANI-SA nanostructures.…”
Section: Introductionmentioning
confidence: 99%